Universalism of Human Rights: Notion of Global Consensus or Regional Idea - Orzeszyna, Krzysztof (Review of European and Comparative Law, 2021)
This article deals with the universal nature of human rights recognised by all civilisations and legal systems. The important thing is that the actions of the state are consistent with the content of these rights is justified by the fact that they protect the dignity of every human being and enable cooperation between people. Universal treaties impose the same international legal obligations in the field of human rights on as many states as possible. Regional treaties perform this function in relation to a group of states. It seems, however, that for the full protection of an individual’s rights, the ideas of universalism and regionalism of human rights need to complement each other. No regional system can exist if it is inconsistent with the norms and principles of the Universal Declaration of Human Rights.